Mine waste rock as a soil amendment for enhanced weathering, ecosystem services, and bioenergy production - Russell, Mackenzie D.; Heckman, Katherine A.; Pan, Lei; Ye, Xinyu; Zalesny, Ronald S.; Kane, Evan S. (Frontiers in Earth Science, 2024)
Enhanced weathering of terrestrial rock material is a promising method for the removal of anthropogenic CO2 emissions from the atmosphere. Herein, we demonstrate that an ameliorated mining waste product can be effectively weathered in the soil environment when used as a soil amendment in conjunction with the cultivation of fast-growing willows (Salix matsudana Koidz. ⨯ S. alba L. “Austree”) in a pot study environment. Utilizing this locally sourced amendment minimizes emissions associated with grinding and transportation of enhanced weathering materials. Results showed that the willows were able to tolerate the relatively high metal concentrations of this amendment and sequester inorganic carbon (C) through the production of bicarbonate in soil solution. During the period of peak plant growth (10 weeks after planting), alkalinity measurements of soil solution from pots with willows and the addition of 25% by mass mine waste product indicated an additional 10 mg of inorganic C sequestration per liter of leached soil solution compared to unamended soils with willows. This represents 4.5 times the inorganic C sequestration rate of unamended soils. The addition of ameliorated mining waste also increased the pH of the soil solution by up to two units (pH of 6 in control vs. pH of 8 with the addition of 25% by mass mineral amendment). In addition to inorganic C sequestration, weathering of the ameliorated mining waste product may also provide base cations (such as calcium and magnesium) which could improve soil fertility. These results are encouraging for future investigation of ameliorated mine waste rock to sequester carbon and enhance the production of willows grown for ecosystem services and phytotechnologies.